1992
DOI: 10.1523/jneurosci.12-01-00204.1992
|View full text |Cite
|
Sign up to set email alerts
|

Cervicothalamic tract terminals are enriched in glutamate-like immunoreactivity: an electron microscopic double-labeling study in the cat

Abstract: The distribution of glutamate-like immunoreactivity (Glu-LI) in the thalamic ventral posterolateral nucleus (VPL) of cats was studied with the EM immunogold technique in order to identify nerve terminal populations that may use glutamate as a neurotransmitter. The investigation was focused on cervicothalamic tract (CTT) terminals, which were labeled by WGA-HRP transported anterogradely from injection sites in the lateral cervical nucleus (LCN). The amount of Glu-LI in different profiles was evaluated quantitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
0

Year Published

1994
1994
2010
2010

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(23 citation statements)
references
References 55 publications
(96 reference statements)
2
21
0
Order By: Relevance
“…Thus, striatal profiles containing the most intense glutamate labeling were axon terminals forming asymmetric synapses, typical of cortical and thalamic input (Kemp and Powell, 1971). In agreement with previous studies in the hippocampus and the cerebellum, many gold particles in boutons were associated with synaptic vesicles (Somogyi et al, 1986;Broman and Ottersen, 1992;. Consistent with the fact that glutamate also exists in nontransmitter pools, for example, as a participant in intermediary metabolism (Fonnum, 1984), glutamate labeling was also observed in several other subcellular compartments.…”
Section: Discussionsupporting
confidence: 91%
“…Thus, striatal profiles containing the most intense glutamate labeling were axon terminals forming asymmetric synapses, typical of cortical and thalamic input (Kemp and Powell, 1971). In agreement with previous studies in the hippocampus and the cerebellum, many gold particles in boutons were associated with synaptic vesicles (Somogyi et al, 1986;Broman and Ottersen, 1992;. Consistent with the fact that glutamate also exists in nontransmitter pools, for example, as a participant in intermediary metabolism (Fonnum, 1984), glutamate labeling was also observed in several other subcellular compartments.…”
Section: Discussionsupporting
confidence: 91%
“…These results indicate that the LPBd contains neurons that transmit cutaneous warm signals directly to the POA. The idea that this activation of warm-responsive LPBd neurons is caused by a glutamatergic input from second-order somatosensory neurons in the spinal dorsal horn is supported by previous anatomical evidence: (i) There are numerous projections from the dorsal horn to the LPB (21), some of which terminate on POAprojecting LPB neurons (8); and (ii) a substantial population of dorsal horn neurons provide their axon collaterals both to the LPB and thalamus (22), and their terminals in the thalamus contain glutamate (23).…”
Section: Discussionmentioning
confidence: 55%
“…However, there is considerable evidence that glutamate is highly concentrated in axonal boutons from which it is released as a transmitter, and that the presence of high levels of glutamate-11 in axon terminals provides one of the most reliable ways of identifying glutamatergic neurons (Somogyi et al, 1986;Montero and Wenthold, 1989;Maxwell et al, 1990;Broman and Ottersen, 1992). By identifying the axons of particular neurons and estimating the level of glutamate-L1 in them, it should therefore be possible to determine whether or not the cells use glutamate as a transmitter.…”
Section: Discussionmentioning
confidence: 99%
“…In the cerebellum it has been shown that the level of glutamate-11 is significantly higher in mossy and parallel fiber terminals (which are thought to release glutamate) than in other cellular compartments, including granule cell bodies that give rise to parallel fibers (Somogyi et al, 1986). Elsewhere in the CNS enrichment of glutamate-L1 has been demonstrated in axon terminals that are thought to be glutamatergic (e.g., Montero and Wenthold, 1989;Maxwell et al, 1990;Broman and Ottersen, 1992). This suggests that within axon terminals it is possible to identify the "transmitter pool" of glutamate.…”
mentioning
confidence: 99%